2008
DOI: 10.1128/iai.01141-07
|View full text |Cite
|
Sign up to set email alerts
|

Flagellin-Dependent and -Independent Inflammatory Responses following Infection by EnteropathogenicEscherichia coliandCitrobacter rodentium

Abstract: Enteropathogenic Escherichia coli (EPEC) and the murine pathogen Citrobacter rodentium belong to the attaching and effacing (A/E) family of bacterial pathogens. These noninvasive bacteria infect intestinal enterocytes using a type 3 secretion system (T3SS), leading to diarrheal disease and intestinal inflammation. While flagellin, the secreted product of the EPEC fliC gene, causes the release of interleukin 8 (IL-8) from epithelial cells, it is unclear whether A/E bacteria also trigger epithelial inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
84
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(101 citation statements)
references
References 48 publications
(62 reference statements)
14
84
0
1
Order By: Relevance
“…We were also able to show that EPEC inhibits proinflammatory cytokine expression by human PP cells. These results support data obtained on rabbit enterocytes (6) and human epithelial cell lines cells (9)(10)(11), which showed a type III secretion dependent reduction of IL-8 production. Similar results were recently reported for EHEC, which can downregulate the proinflammatory cytokine production by intestinal epithelial cells in response to its own Shiga toxin (20) and uses the effector NleH1 to subvert NF-kB-dependent transcription by binding to the ribosomal protein s3 (21).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We were also able to show that EPEC inhibits proinflammatory cytokine expression by human PP cells. These results support data obtained on rabbit enterocytes (6) and human epithelial cell lines cells (9)(10)(11), which showed a type III secretion dependent reduction of IL-8 production. Similar results were recently reported for EHEC, which can downregulate the proinflammatory cytokine production by intestinal epithelial cells in response to its own Shiga toxin (20) and uses the effector NleH1 to subvert NF-kB-dependent transcription by binding to the ribosomal protein s3 (21).…”
Section: Discussionsupporting
confidence: 81%
“…However, other work suggests that the situation is more complex, and that EPEC can also reduce cytokine production (8)(9)(10)(11). Because inhibition of cytokine production is dependent on a functional T3SS (8)(9)(10)(11), EPEC may also inject inhibitory effector proteins into epithelial cells.…”
mentioning
confidence: 99%
“…CI, confidence interval. inflammation and pathology following neutrophil infiltration (24,28,43,44). This inconsistency may reflect the innate immune system's ability to provide a protective response but also produce negative consequences, including exacerbated tissue destruction, following the hyperactivation of this system (28).…”
Section: Discussionmentioning
confidence: 99%
“…Although EPEC strains are not invasive pathogens, they induce an inflammatory response in the gut epithelium in vivo by triggering production of cytokines and chemokines, including IL-8, which recruits polymorphonuclear leukocytes to the infection site (24). In vitro studies have shown that intestinal epithelial cells infected with EPEC trigger IL-8 release through Toll-like receptor 5 (TLR-5) and activation of NF-B, mediated by flagellin, the secreted protein of the EPEC fliC gene (16). In addition, NleE, a type 3 secretory system (T3SS) effector, is required for EPEC-induced polymorphonuclear leukocyte migration (28).…”
Section: Discussionmentioning
confidence: 99%